2013
DOI: 10.2741/e656
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction -mediated cAMP movement between oocytes and somatic cells

Abstract: Cyclic AMP (cAMP) plays a critical role in oocyte meiotic maturation. However, the source of cAMP surge prior to maturation and the direction of gap junction-dependent cAMP movement are unclear. In this study, inhibition of gap junctional communication (GJC) using carbenoxolone (3.5 h) induced meiotic resumption in ~90% of follicle-enclosed oocytes (FEOs). The concentration of cAMP in a single oocyte was higher than that in a single cumulus cell, suggesting that the movement of cAMP proceeds from the oocyte to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Studies in mammalian systems have suggested that cyclic nucleotides can also pass through gap junctions to affect cellular function. For example, cAMP movement between cells has been visualized following ectopic expression of gap junction components in human tissue culture [ 29 , 74 , 75 ]. cAMP movement through gap junctions also suppresses CD4+ T-cell function [ 76 ] and may alter gene expression in myelinating Schwann cells [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mammalian systems have suggested that cyclic nucleotides can also pass through gap junctions to affect cellular function. For example, cAMP movement between cells has been visualized following ectopic expression of gap junction components in human tissue culture [ 29 , 74 , 75 ]. cAMP movement through gap junctions also suppresses CD4+ T-cell function [ 76 ] and may alter gene expression in myelinating Schwann cells [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…cAMP movement through gap junctions also suppresses CD4+ T-cell function [ 76 ] and may alter gene expression in myelinating Schwann cells [ 77 ]. In addition, cGMP can pass through gap junctions in human cell culture, as well as between cultured mouse follicle cells and oocytes [ 29 , 30 , 32 , 78 ]. While 25 innexins are encoded by the C .…”
Section: Resultsmentioning
confidence: 99%
“…The cumulus cells continue the important role of supporting the development of the growing oocyte and its eventual acquisition of competence to form an embryo with high developmental potential. Specifically, cumulus cells sense and respond to maternal endocrine and paracrine signals to produce energy, cyclic nucleotides (cAMP and cGMP), and RNA and transfer these to the oocyte via gap junctions ( 176 , 177 ). These factors regulate oocyte meiotic arrest/resumption through cell cycle-regulating complexes ( 178 180 ).…”
Section: Folliculogenesismentioning
confidence: 99%
“…It has been well-known that COCs not only secrete paracrine factors but they also interact through the gap junctions (passing molecules only smaller than 1 kDa, [8]) in a bidirectional manner, which is essential for oocyte nutrition, growth, and regulation of meiotic progression [9][10][11]. Also, CCs contribute partially to maintain the oocyte into meiotic arrest by the production and transfer of cAMP via gap junctions, which accumulates into the ooplasm [12]. The communication through the gap junctions between the oocyte and CCs decreases progressively during IVM [13,14].…”
Section: Introductionmentioning
confidence: 99%